Development of efficient protocols to generate breast cancer spheroids for application in drug discovery - Ntsoyi, Nomaphelo Ntombikayise (Rhodes University, Faculty of Science, Biotechnology Innovation Centre)
Restricted access. Expected release in 2026.
Keywords: Uncatalogued